Advancing Towards a Sustainable Future: A Systematic Review of Sustainable Net Zero Economy Implementation Studies - Vihas Vijay; Sathish A.S. (Qubahan Academic Journal)
This systematic review, adhering to the PRISMA framework, critically analyses 22 peer-reviewed articles from the Scopus database, focusing on Sustainable Net Zero Economy Implementation (SNZEI). Spanning publications from 2017 to 2023, this study encapsulates the evolving landscape of SNZEI research, highlighting its interdisciplinary nature and diverse methodological approaches. The findings reveal a strong emphasis on practical applications across energy, transportation, and urban planning sectors, underpinned by robust theoretical frameworks such as risk assessment, technology adoption, and educational theories. A significant gap is identified in research from developing economies, suggesting an avenue for further exploration, particularly in high-impact industries like pharmaceuticals. The review advocates for global collaboration and interdisciplinary strategies to transition towards sustainable net-zero economies, providing insights for researchers, policymakers, and industry stakeholders. They offer actionable insights and recommendations, stressing the need for comprehensive policy analysis and technological innovation. This review not only provides a current snapshot of SNZEI research but also charts a course for future studies, underscoring the need for global collaboration and interdisciplinary strategies to effectively transition towards sustainable, net-zero economies. These insights are pivotal for researchers, policymakers, and industry stakeholders in their collective efforts to address climate change and promote environmental sustainability.